BDNF Val66Met polymorphism is not related with temporal lobe epilepsy caused by hippocampal sclerosis in Brazilian population. (August 2018) - Alcantara, Juliana A.; Vincentiis, Silvia; Santos, Bernardo; Kerr, Daniel; de Paula, Vanessa; Alessi, Ruda; Linden, Helio; Chaim, Tiffany; Serpa, Maurício; Busatto, Geraldo; Gattaz, Wagner; Valente, Kette D.
Abstract: Purpose: Some variants of the brain derived neurotrophic factors (BDNF) gene, namely the Val66Met (rs6265), may contribute the risk for epilepsy development. We aimed to investigate if this polymorphism was associated with the risk for epilepsy development in TLE-HS and its correlation with epilepsy-related factors and the presence of psychiatric disorders. Methods: We assessed 119 patients with unequivocal TLE-HS and 112 healthy controls. Individuals were genotyped for the polymorphisms of the gene encoding BDNF Val66Met. Results: There was no difference between TLE-HS and healthy controls, for the genotypic distribution (p = 0.636) and allelic distribution (p = 0.471). There was no correlation between Val66Met and epilepsy-related factors and for psychiatric comorbidities (p = 0.888). Conclusions: Our findings demonstrated that polymorphism Val66Met is not associated with TLE-HS, epilepsy-related factors and psychiatric comorbidities in this selected group of patients.